Creative Thinking dalam Manajemen Seni Dangdut Kontemporer Grup “Pasukan Perang” - Rini Nur Mega; Endang Caturwati; Suhendi Afryanto (PANTUN, 2021)
This paper examines the management of a music group ‘Pasukan Perang’, the Dangdut Orchestra band, in Bandung city. The goal is to reveal the management process in breaking down the music industry in Indonesia and the world in general. Alfred Schutz's phenomenological theory is applied to provide the overview of art management based on creative thinking and work structure innovation to measure the achievement of success. The data were collected through conducting in-depth interviews; reflecting thoughts to seek meaning and a frame of reference for symptoms; constructing the meaning and essence. The results of the analysis show that the Dangdut Music group “Pasukan Perang” is a prism to view Indonesian society. Its existence reflects the state of national culture in economic, political, and ideological practices. It contributes to shape ideas of class, gender, and ethnicity in the modern era. “Pasukan Perang” touches various musical genres so that it becomes a Contemporary Dangdut Icon nicknamed the Loving Band Group.Keywords: creative thinking, contemporary dangdut, war troops, art management